Green's function for an anisotropic piezoelectric half-space bonded to a thin piezoelectric layer - Chung, M.Y. (Archives of Mechanics, 2014)
The Green's function for an anisotropic piezoelectric half-space bonded to a thin piezoelectric layer subject to a generalized line force and a generalized line dislocation is presented. The thickness of a thin layer is assumed to be small compared with a reference length. Thus, the existence of the layer is replaced by effective boundary conditions to avoid finding solutions in the layer. Combining with the Stroh formalism gives explicit solutions in a more compact form.